2013
DOI: 10.1002/jgre.20063
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the global composition of the lunar surface from high‐energy gamma rays measured by Lunar Prospector

Abstract: [1] An analysis of the lunar gamma-ray spectrum as measured by the Lunar Prospector Gamma-Ray Spectrometer has revealed that 8-8.9 MeV gamma rays contain information about the elemental composition of near-surface materials. These high-energy gamma rays are found to be primarily sensitive to the total Fe and Mg content of the surface, although other elements also contribute. This information has been used to identify several regions with unique compositions, including the Hertzsprung and Orientale basins. A me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…For example, certain compositions might show biases to retain hydrogen more effectively than other compositions. While the bulk iron and titanium abundances across the FHT are mostly uniformly low (Lucey et al, 2000b;Lawrence et al, 2002), other bulk composition parameters, such as magnesium concentrations, do appear to show significant variations across the FHT (Prettyman et al, 2006;Peplowski and Lawrence, 2013) and in principle could be linked to compositional effects related to hydrogen retention. More recent measures of optical maturity (Nettles et al, 2011) show different compositional variations that can be compared to the derived hydrogen concentrations.…”
Section: Discussion Conclusion and Future Workmentioning
confidence: 91%
“…For example, certain compositions might show biases to retain hydrogen more effectively than other compositions. While the bulk iron and titanium abundances across the FHT are mostly uniformly low (Lucey et al, 2000b;Lawrence et al, 2002), other bulk composition parameters, such as magnesium concentrations, do appear to show significant variations across the FHT (Prettyman et al, 2006;Peplowski and Lawrence, 2013) and in principle could be linked to compositional effects related to hydrogen retention. More recent measures of optical maturity (Nettles et al, 2011) show different compositional variations that can be compared to the derived hydrogen concentrations.…”
Section: Discussion Conclusion and Future Workmentioning
confidence: 91%
“…). Examination of LP GRS data (Peplowski and Lawrence ) found that, for gamma rays with energies between 8 and 8.9 MeV, the continuum originated predominantly from the lunar surface. Unlike the LP measurements, the GRaND gamma‐ray measurements include an appreciable background contribution from the spacecraft at all energies and therefore require a background reduction process that was not necessary for the LP HEGR measurements.…”
Section: Background Informationmentioning
confidence: 99%
“…Peplowski and Lawrence () used the laboratory measured charged pion production cross sections (σ) of Cochran et al. () to express the total, element‐dependent pion production cross section σ i (π) asσi(π)=32[24.3Zi1/3+2.33Ni2/3] where Z i and N i are the proton and neutron numbers of element i , respectively, and the units are millibarns (1 mb = 10 −27 cm 2 ).…”
Section: Background Informationmentioning
confidence: 99%
See 2 more Smart Citations